(untitled) (Società e diritti, 2016)
The text presents the main comments to the theses of Prof. Catelani expressed at the seminar held at the University of Milan on 28 January 2016 and on the occasion of the meeting of May 4, 2016 held in Brixen. Key words: fundamental rights, public administration, legal positivism.